Epidemiology of yellow fever virus in humans, arthropods, and non-human primates in sub-Saharan Africa: A systematic review and meta-analysis. - Martin Gael Oyono; Sebastien Kenmoe; Ngu Njei Abanda; Guy Roussel Takuissu; Jean Thierry Ebogo-Belobo; Raoul Kenfack-Momo; Cyprien Kengne-Nde; Donatien Serge Mbaga; Serges Tchatchouang; Josiane Kenfack-Zanguim; Robertine Lontuo Fogang; Elisabeth Zeuko'o Menkem; et al. (Public Library of Science (PLoS), 2022)
Yellow fever (YF) has re-emerged in the last two decades causing several outbreaks in endemic countries and spreading to new receptive regions. This changing epidemiology of YF creates new challenges for global public health efforts. Yellow fever is caused by the yellow fever virus (YFV) that circulates between humans, the mosquito vector, and non-human primates (NHP). In this systematic review and meta-analysis, we review and analyse data on the case fatality rate (CFR) and prevalence of YFV in humans, and on the prevalence of YFV in arthropods, and NHP in sub-Saharan Africa (SSA). We performed a comprehensive literature search in PubMed, Web of Science, African Journal Online, and African Index Medicus databases. We included studies reporting data on the CFR and/or prevalence of YFV. Extracted data was verified and analysed using the random effect meta-analysis. We conducted subgroup, sensitivity analysis, and publication bias analyses using the random effect meta-analysis while I2 statistic was employed to determine heterogeneity. This review was registered with PROSPERO under the identification CRD42021242444. The final meta-analysis included 55 studies. The overall case fatality rate due to YFV was 31.1% (18.3-45.4) in humans and pooled prevalence of YFV infection was 9.4% (6.9-12.2) in humans. Only five studies in West and East Africa detected the YFV in mosquito species of the genus Aedes and in Anopheles funestus. In NHP, YFV antibodies were found only in members of the Cercopithecidae family. Our analysis provides evidence on the ongoing circulation of the YFV in humans, Aedes mosquitoes and NHP in SSA. These observations highlight the ongoing transmission of the YFV and its potential to cause large outbreaks in SSA. As such, strategies such as those proposed by the WHO's Eliminate Yellow Fever Epidemics (EYE) initiative are urgently needed to control and prevent yellow fever outbreaks in SSA.